PIAT DEVELOPMENT TOWARDS WELLNESS TOURISM WITH KANSEI ENGINEERING AND KANO MODELS - Istikomah, Sintha; Ushada, Mirwan; Masruroh, Nur Aini (Master in Systems Engineering, 2022)
Wellness tourism is one of the efforts to revive the Indonesian tourism sector during the transition period of the pandemic to endemic. People seek prevention and health maintenance by traveling to get a better quality of life. Giving rise to wellness tourism as wellness and health tourism in the form of health care based on a healthy natural environment and restoration of relaxation. One of the innovations carried out by PIAT is the development of agro-industry by applying the concept of wellness tourism. Tourist attractions will be more valuable if they can meet the needs of the highest level, namely pleasure. This study aims to: (1) identify the words Kansei of prospective tourists related to wellness tourism. (2) determine the concept model of wellness tourism atmosphere design that suits the pleasure needs of tourists. (3) improve the products and services of the Agrotechnology Innovation Center (PIAT) based on the priority attribute of tourist needs. This research used the Kansei engineering method and the kano model. Semantic Differential (SD) Questionnaire 1 to capture images of wellness attractions. Kansei engineering begins with the collection of tourist pleasure needs in the form of Kansei word, simplifying Kansei word with factor analysis, categorization analysis of Kano models, identification of technical attributes, dissemination of SD 2 questionnaires and questionnaire analysis with quantification theory 1 (QT1) to determine the correlation between tourist attributes and design concepts quantitatively. The results obtained from the first questionnaire, there are nine Kansei words that describe wellness tourism places at PIAT UGM, namely